Prevalence, Causes, and Management Strategies of Fungal Diseases in Northern Regions of Bangladesh - Akanda, Md. Khokon Miah; Sultana, Razia; Rana, Md. Masud; Hossain, Md. Alamgir; Barik, S. M. Abdul; Islam, Md. Rafiul; Islam, Md. Nazmul; Parvez, G.M. Masud (Sciences of Pharmacy, 2024)
In Bangladesh, fungus-related skin diseases are highly prevalent. Until this result began, there was no research in Bangladesh to find the cause and management strategies for fungal infection, but there is still no complete research on it. This survey aimed to evaluate the incidence, etiology, and therapeutic alternatives for various fungal ailments in Bangladesh. The research was carried out in Rajshahi from January to June 2019 by the Pharmacy Department of Varendra University. A compilation of 489 patient data was obtained throughout the investigation using a semi-structured questionnaire. The participants' ages vary from three months to seventy years; 327 are male, and 162 are female. The most prevalent skin conditions among the patients are as follows: ringworm (11.25%), skin infections affecting the ear, nose, fingers, and uterus (11.04%), acne (8.19%), allergy (9.82%), dandruff (5.11%), dermatitis (9.00%), eczema (5.73%), and scabies (7.18%). Student individuals comprise 49.28% of the patients, day workers 16.56%, housewives 16.36%, and employed 14.31%. Patients are housed in 53.17 percent concrete houses, 26.5 percent huts, and 26.18% semi-structures. Patients wash their clothing with tap water at a rate of 52%, followed by tube well water at 21.27%, pond water at 20.45%, and river water at 5.52%. It is evident from this study that fungal diseases affect individuals of all ages, including men and women. An adverse finding of the research was that over forty percent of patients do not receive accurate instructions from their physicians, which raises the risk of drug resistance and further contamination.